BAL and non-BAL quasars: continuum, emission, and absorption properties establish a common parent sample. Issue 3 (16th January 2020) - Rankine, Amy L; Hewett, Paul C; Banerji, Manda; Richards, Gordon T
ABSTRACT: Using a sample of ≃144 000 quasars from the Sloan Digital Sky Survey Data Release 14, we investigate the outflow properties, evident in both absorption and emission, of high-ionization broad absorption line (BAL) and non-BAL quasars with redshifts 1.6 ≲ z ≤ 3.5 and luminosities 45.3 erg s −1 < log10 ( L bol ) < 48.2 erg s −1 . Key to the investigation is a continuum and emission-line reconstruction scheme, based on mean-field independent component analysis, that allows the kinematic properties of the C iv λ1550 emission line to be compared directly for both non-BAL and BAL quasars. C iv emission blueshift and equivalent width (EW) measurements are thus available for both populations. Comparisons of the emission-line and BAL trough properties reveal strong systematic correlations between the emission and absorption properties. The dependence of quantitative outflow indicators on physical properties such as quasar luminosity and luminosity relative to Eddington luminosity is also shown to be essentially identical for the BAL and non-BAL populations. There is an absence of BALs in quasars with the hardest spectral energy distributions (SEDs), revealed by the presence of strong He ii λ1640 emission, large C iv λ1550 emission EW, and no measurable blueshift. In the remainder of the C iv emission blueshift versus EW space, BAL and non-BAL quasars are present at all locations; for every BAL quasar, it is possible to identify non-BAL quasars with the same emission-line outflow properties and SED hardness. The co-location of BAL and non-BAL quasars as a function of emission-line outflow and physical properties is the key result of our investigation, demonstrating that (high-ionization) BALs and non-BALs represent different views of the same underlying quasar population.